Biology and Culture of Percid Fishes 2015
DOI: 10.1007/978-94-017-7227-3_16
|View full text |Cite
|
Sign up to set email alerts
|

Culture Methods of Eurasian Perch During Ongrowing

Abstract: Three different production systems are used for perch ongrowing: (1) traditional extensive polyculture system, (2) semi-intensive culture farming and (3) intensive perch farming under RAS (Recirculating Aquaculture System(s)). Extensive and semi-intensive culture systems have many production limitations. Therefore, intensive perch farming has been developed in Europe for more continuous and predictive marketable perch production.Marketable perch production under RAS is affected by several main factors of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…Lowering and increasing the tank water level as required for cleaning and water renewal, water flow and aeration can disturb larvae buoyancy or cause injury or death of larvae possibly due to changes in hydrostatic pressure, turbulences, or mechanical forces. The perch is a physoclistous fish and the initial inflation of the swimbladder and the closure of the pneumatic duct occur at 6-12 dph (Eglof, 1996;Policar, Samarin, & Mélard, 2015). Woolley and Qin (2010) suggested that larvae might be especially vulnerable to changes in hydrostatic pressure during the period of swimbladder development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Lowering and increasing the tank water level as required for cleaning and water renewal, water flow and aeration can disturb larvae buoyancy or cause injury or death of larvae possibly due to changes in hydrostatic pressure, turbulences, or mechanical forces. The perch is a physoclistous fish and the initial inflation of the swimbladder and the closure of the pneumatic duct occur at 6-12 dph (Eglof, 1996;Policar, Samarin, & Mélard, 2015). Woolley and Qin (2010) suggested that larvae might be especially vulnerable to changes in hydrostatic pressure during the period of swimbladder development and differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…From these experiments it was concluded that a homogenous live feed was necessary as starter feed for perch larvae. Paramecium caudatum fulfilled the necessary criteria as it had an adequate size (length 120-220 µm, width 60-120 µm- Fokin, 1997) to be ingested by perch larvae, which mouth size is 0.35 mm (Policar, Samarin, & Mélard, 2015). However, growth of perch larvae fed with Paramecium caudatum was moderate in comparison to zooplankton, indicating a decreased nutritional value.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The perch were trained to consume formulated feed. The feed used was manufactured by Nutreco (Nutra, Trouvit, France), and the feeding procedure was similar to that reported by Policar et al (2015). The fish were reared under these conditions for approximately ten weeks until they had reached approximately 10 g BW.…”
Section: Fish and Rearing Conditionsmentioning
confidence: 99%